Hunter's moon - Townsend, John, 1955- (Stone Arch Books, 2007)
As Halloween approaches, Neil has a growing fear of the woods on the farm where he is filling in as gamekeeper since, besides the rumor that a big cat is loose, he has also received a warning to "beware the nights of the Hunter's Moon" which are about to begin.